Taxonomy and natural history of arboreal microhylid frogs (Platypelis) from the Tsaratanana Massif in northern Madagascar, with description of a new species - Rakotoarison, Andolalao; Glaw, Frank; Vieites, David R.; Raminosoa, Noromalala R.; Vences, Miguel (Zootaxa, 2012)
We review the taxonomic status of microhylid frogs of the genus Platypelis occurring on the Tsaratanana mountain rangein northern Madagascar. Two species have originally been described from the region, Platypelis alticola and P.tsaratananaensis. We found P. alticola at elevations from 1589–2429 m, with the population at 1589 m being geneticallydivergent (pairwise sequence divergence in the 16S rRNA gene fragment 3.8%). The species was mainly found in bamboosegments accessible via small holes, and its vocalization was a tonal single-note call repeated in long regular series. Theidentity of P. tsaratananaensis was uncertain for many years. Based on comparisons with the type material we concludethat the name should be applied to a common species in the Tsaratanana region morphologically similar to P. pollicarisbut distinguished by a double-note advertisement call, repeated in long series in P. tsaratananaensis (vs. single-note in P.pollicaris), relative length of toes, and size of the prepollex in males (larger in P. pollicaris). Populations of P.tsaratananaensis from several nearby forests were genetically similar to those from the main Tsaratanana Massif. Thespecies is nidicolous with 1–27 embryos and non-feeding larvae in waterfilled bamboo segments. Oocyte number iscorrelated with female size, and larger adult specimens were found in bamboo segments situated higher above the ground.A new species, Platypelis olgae sp. nov., is described from two sites at ca. 2500 m elevation on the Tsaratanana, based onits genetic and morphological differentiation. It differs from other Platypelis by small body size (adult snout-vent length20–22 mm) the absence or rudimentary state of vomerine teeth, green to yellow ventral color, and absence of contrastingand sharply delimited symmetrical dark dorsal patches. Platypelis alticola, P. tsaratananaensis and P. olgae sp. nov. were regularly parasitized by mites probably of the genus Endotrombicula.